Physiotherapy and rehabilitation center for people with temporary and perennial physical disabilities of the Province of Tacna located in the District of Gregorio Albarracín Lanchipa - Schiaffino Miovich, Andrea Melissa (2015)
Objective: To design a specialized infrastructure for the physiotherapy and rehabilitation center for people with temporary and perennial disabilities in the province of Tacna, improving the provision of physical health services. Materials and Methods: The methodology used in the research was descriptive-analytical-propositional, by means of which a diagnosis was formulated that led to the approach to the architectural project was formulated. Results: As a result of the research Project considering their respective architectural foundation was developed. Conclusions: The final approach of our architectural proposal and adapting to the urban parameters of the environment with the appropriate physical and formal treatment for a better special integration without generating visual or environmental impacts that affect third parties.